The Development of Training Center as a Novel Business Concept - Ng Wei Chien; Gan Kia Hui; Muhammad Aidil Muqris Bin Azizi; Muhamad Ammar Danial Bin Sabdan; Ma Xiaomengying; Miao Jiayi; Khushi Dubey (AIBPM Publisher, 2024)
The objective of this study is to evaluate the effectiveness of innovative training methods, technology integration, personalized training, and strategic partnerships in enhancing business performance through the Qatar Skills Training Centre (QSTC). Employing quantitative methods, data were collected through a survey distributed via Google Forms, with responses from 154 participants representing various socio-economic backgrounds. The analysis revealed that while strategic partnerships did not significantly affect business performance, innovative training methods, technology integration, and personalized training demonstrated positive correlations with business success, supporting Hypotheses 1, 2, and 3. The results showed beta values of 0.588, 0.246, and 0.188 for these factors, respectively, and an R² value of 0.92, indicating that 92% of the variance in business performance is attributable to these elements. This highlights the critical role of innovative training methods, technology, and personalization in driving successful business strategies. The findings suggest that organizations should prioritize these factors to enhance employee engagement, satisfaction, and overall operational effectiveness.